International reserves and gross capital flows dynamics. (February 2016) - Alberola, Enrique; Erce, Aitor; Serena, José Maria
Highlights: This paper explores the role of international reserves as a stabilizer of gross capital flows during financial stress. During stress, international reserves facilitate financial disinvestment overseas by residents. This partially offsets the drop in foreign capital inflows observed in such periods. These results suggest reserve adequacy measures should take into account the behaviour of resident investors. Abstract: This paper explores the role of international reserves as a stabilizer of international capital flows, in particular during periods of global financial stress. In contrast with previous contributions, aimed at explaining net capital flows, we focus on the behavior of gross capital flows. We analyze an extensive cross-country quarterly database – 63 countries, 1991–2010 – using standard panel regressions. We document significant heterogeneity in the response of resident investors to financial stress and relate it to a previously undocumented channel through which reserves act as a buffer during financial stress. A robust result of the analysis is that international reserves facilitate financial disinvestment overseas by residents – a fall in capital outflows. This partially offsets the drop in foreign capital inflows observed in such periods. For the whole sample, we also find that larger stocks of international reserves are linked to higher gross inflows and lower gross outflows. These results, which challenge current approaches to measuring reserve adequacy, call for refining such tools to better account for the role of resident investors.